The Fall in German Unemployment: A Flow Analysis - Carlos Carrillo-Tudela; Andrey Launov; Jean-Marc Robin (Center for Economic Studies and Ifo Institute (CESifo), 2020)
In this paper we investigate the recent fall in unemployment, and the rise in part-time work and labour market participation amongst prime-aged Germans. We show that unemployment fell because the Hartz reforms induced a large fraction of the long-term unemployed to deregister as jobseekers. However, labour force participation actually increased because many female non-participants accepted low-paid, part-time jobs. Counterfactual simulations using estimated transition probabilities show that observed changes in the stocks of registered and unregistered unemployment as well as marginal, contributed part-time and full-time employment after 2002 essentially resulted from changes in registered and unregistered unemployment outflows. Yet to obtain the full decrease in registered male unemployment, we need to account for the effect of wage moderation. A calibrated Diamond-Mortensen-Pissarides model suggests that wage moderation is at most half as strong as the unemployment reforms in explaining changes in unemployment, non-participation and part-time employment.
Keywords: J21; J31; J63; J64; 330; unemployment; part-time work; mini-jobs; non-participation; wage moderation; Hartz reforms